Occupational Therapy Stays in Healthcare Institutions in the Slovak Republic - best practice or not? - Žuľová, Jana; Švec, Marek (Technium Social Sciences Journal, 2020)
The legislation establishes a general principle for the employer with respect to prevention and assurance of health and safety at work, including the elimination of risks and factors that may lead to accidents at work, occupational diseases and other damage to health at work. The employer should prevent possible damage to the employee’s health by taking various technical and organizational measures to protect the health of employees. In the conditions of the Slovak Republic, measures of this type include stays in institutions providing occupational healthcare. The scientific paper summarizes the substantive conditions of the employee’s right to receive occupational therapy in institutional care, it points out the application shortcomings of the current legislation and, at the same time, criticizes the legislation adopted in connection with measures to prevent the spread of corona virus, which complicates the process of granting the employee their right to receive occupational therapy in institutional care. The aim is to provide scrutiny of this institute in the area of employee health and safety at work as a specific feature of the Slovak legislation. From the experience of the Slovak application practice, the authors are inclined to believe that occupational therapy provided in institutional care is a socialist relic in a market economy rather than an inspiring best practice for European legislators.